2009
DOI: 10.1161/circulationaha.108.848143
|View full text |Cite
|
Sign up to set email alerts
|

Functional Lecithin: Cholesterol Acyltransferase Is Not Required for Efficient Atheroprotection in Humans

Abstract: Background-Mutations in the LCAT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 30 publications
4
44
3
4
Order By: Relevance
“…However, we previously showed that carotid wall thickness measured with MRI and ultrasound is enhanced compared to controls suggesting accelerated atherosclerosis [7]. Contrary to our previous report, Calabresi et al have shown a decreased carotid wall thickness in LCAT mutation carriers [6,7]. These seemingly conflicting results might be explained by differences in gene mutations.…”
Section: Strengths and Weaknessescontrasting
confidence: 82%
See 1 more Smart Citation
“…However, we previously showed that carotid wall thickness measured with MRI and ultrasound is enhanced compared to controls suggesting accelerated atherosclerosis [7]. Contrary to our previous report, Calabresi et al have shown a decreased carotid wall thickness in LCAT mutation carriers [6,7]. These seemingly conflicting results might be explained by differences in gene mutations.…”
Section: Strengths and Weaknessescontrasting
confidence: 82%
“…In this respect, two ultrasound studies reached opposite conclusions, one study reporting increased intima media thickness (IMT) in the carotid arteries of carriers as a surrogate outcome for atherosclerosis [5] and the other reporting decreased IMT in carotid arteries of carriers compared controls [6]. We have recently confirmed the findings of our earlier study by showing structural abnormalities in the carotid arteries of LCAT mutation carriers with low HDL-c compared to matched controls using both ultrasound and 3.0 T magnetic resonance imaging of the carotid arteries [7].…”
Section: Introductionmentioning
confidence: 99%
“…Three IMT studies have been carried out in carriers of LCAT gene mutations [76][77][78]; altogether, the results suggest that LCAT deficiency does not remarkably increases preclinical atherosclerosis, and according to the Italian study could even be protective for human arteries [78]. The Italian study evaluated 40 carriers of LCAT deficiency (12 homozygotes or compound heterozygotes, and 28 heterozygotes, Table 1) in comparison with 80 matched control subjects [78]; average carotid IMT was 0.07 mm smaller in the carriers than controls (Fig.…”
Section: Inherited Hdl Disorders and Preclinical Atherosclerosismentioning
confidence: 99%
“…The Italian study evaluated 40 carriers of LCAT deficiency (12 homozygotes or compound heterozygotes, and 28 heterozygotes, Table 1) in comparison with 80 matched control subjects [78]; average carotid IMT was 0.07 mm smaller in the carriers than controls (Fig. 2), and the inheritance of a mutated LCAT genotype had a remarkable gene-dose dependent effect in reducing carotid IMT [78].…”
Section: Inherited Hdl Disorders and Preclinical Atherosclerosismentioning
confidence: 99%
“…167 While some studies show association between LCAT levels and AS ). A recent IMT study done by 190 Calabresi et al [26] has found that in carriers of LCAT mutations LCAT 191 deficiency is not associated with increased atherosclerosis. of AS is small.…”
mentioning
confidence: 95%